2008
DOI: 10.1016/j.cell.2008.06.049
|View full text |Cite|
|
Sign up to set email alerts
|

Senescence of Activated Stellate Cells Limits Liver Fibrosis

Abstract: Summary Cellular senescence acts as a potent mechanism of tumor suppression; however, its functional contribution to non-cancer pathologies has not been examined. Here we show that senescent cells accumulate in murine livers treated to produce fibrosis, a precursor pathology to cirrhosis. The senescent cells are derived primarily from activated hepatic stellate cells, which initially proliferate in response to liver damage and produce the extracellular matrix deposited in the fibrotic scar. In mice lacking key… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

50
1,494
4
5

Year Published

2014
2014
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 1,666 publications
(1,598 citation statements)
references
References 35 publications
50
1,494
4
5
Order By: Relevance
“…As our data demonstrate that early passage human fibroblasts with dysfunctional telomeres transdifferentiate into functional myofibroblasts while displaying some features of senescence, they suggest that functional myofibroblasts and senescent (myo)fibroblasts are difficult to distinguish. The observations that fibroblast with senescence features detected in damaged tissue frequently display features of myofibroblasts, such as high expression levels of α‐SMA, are consistent with this conclusion (Jun & Lau, 2010) (Demaria et al, 2014; Krizhanovsky et al, 2008). It is important to note, however, that human fibroblasts serially passaged into replicative senescence and those that underwent oncogene‐induced senescence, both lacked features of myofibroblasts, demonstrating that not all fibroblasts induced to senesce by telomere dysfunction or other stresses are functional myofibroblasts.…”
Section: Discussionsupporting
confidence: 60%
See 2 more Smart Citations
“…As our data demonstrate that early passage human fibroblasts with dysfunctional telomeres transdifferentiate into functional myofibroblasts while displaying some features of senescence, they suggest that functional myofibroblasts and senescent (myo)fibroblasts are difficult to distinguish. The observations that fibroblast with senescence features detected in damaged tissue frequently display features of myofibroblasts, such as high expression levels of α‐SMA, are consistent with this conclusion (Jun & Lau, 2010) (Demaria et al, 2014; Krizhanovsky et al, 2008). It is important to note, however, that human fibroblasts serially passaged into replicative senescence and those that underwent oncogene‐induced senescence, both lacked features of myofibroblasts, demonstrating that not all fibroblasts induced to senesce by telomere dysfunction or other stresses are functional myofibroblasts.…”
Section: Discussionsupporting
confidence: 60%
“…After tissue damage, the transient generation of senescent stromal cells at the site of injury is critical to suppress fibrosis (Jun & Lau, 2010; Krizhanovsky et al, 2008), attract immune modulatory cells (Krizhanovsky et al, 2008), and promote the generation of myofibroblasts in a paracrine manner (Demaria et al, 2014). While the formation of myofibroblasts during wound healing in a mouse model system was reported to be stimulated by SASP factors secreted from senescent fibroblasts and endothelial cells generated at the site of injury (Demaria et al, 2014), other studies demonstrated that, paradoxically, the SASP causes bystander senescence in somatic human fibroblasts (Acosta et al, 2013; Hubackova et al, 2012; Nelson et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…NK cells, macrophages, and cytotoxic CD8 + T cells are chemo‐attracted by the inflamed tissues to promote cell death, thus facilitating senescent cell replacement and a return to tissue homeostasis (Hoenicke & Zender, 2012; Davies et al ., 2013). NK cells are especially important in the immunosurveillance of senescent cells during tissue repair (Krizhanovsky et al ., 2008a,b). They are attracted to senescent cells through a p53‐dependent secretion of CCL2 [chemokine (C‐C) ligand 2] (Iannello et al ., 2013).…”
Section: Cellular Senescence and Immunity In Tissue Homeostasismentioning
confidence: 99%
“…In addition, activated NK cells also produce large amount of IFN-γ, which can induce HSC apoptosis and cell cycle arrest, as well as by enhancing NK cell killing of early activated HSC [131,132]. In addition, NK cells can selectively kill senescent activated HSC, which are cell cycle arrested cells that accumulate in fibrotic septa during chronic liver injury and become inefficient in ECM synthesis but able to up-regulate expression of extracellular matrixdegrading enzymes [133,134]. It has been proposed that senescence-activated HSCs express elevated levels of NK cell-activating ligands, becoming then sensitive to NK cell killing [133].…”
Section: Natural Killer and Natural Killer T Cells In Liver Fibrogenementioning
confidence: 99%